2021
DOI: 10.1007/s00531-021-01982-5
|View full text |Cite
|
Sign up to set email alerts
|

The influence of variations in crustal composition and lithospheric strength on the evolution of deformation processes in the southern Central Andes: insights from geodynamic models

Abstract: Deformation in the orogen-foreland system of the southern Central Andes between 33° and 36° S varies in style, locus, and amount of shortening. The controls that determine these spatially variable characteristics have largely remained unknown, yet both the subduction of the oceanic Nazca plate and the strength of the South American plate have been invoked to play a major role. While the parameters governing the subduction processes are similar between 33° and 36° S, the lithospheric strength of the upper plate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 121 publications
3
13
0
Order By: Relevance
“…The values of thermal parameters are within the range expected for crustal and mantle materials (e.g., Barrionuevo et al., 2021; Sobolev et al., 2006). Radiogenic heat production is 1.0 μW m −3 in the felsic crust and 0.3 μW m −3 in the mafic crust.…”
Section: Numerical Model Descriptionsupporting
confidence: 74%
“…The values of thermal parameters are within the range expected for crustal and mantle materials (e.g., Barrionuevo et al., 2021; Sobolev et al., 2006). Radiogenic heat production is 1.0 μW m −3 in the felsic crust and 0.3 μW m −3 in the mafic crust.…”
Section: Numerical Model Descriptionsupporting
confidence: 74%
“…Changes in the slab shape and age accompany changes in the force balance of the subduction zone as well as the shape of the mantle wedge and lithosphere-asthenosphere boundary underneath the orogen, all of which form a bottom-up control on the direction of tectonic transport and orogen structure (Schellart, 2017;Barrionuevo et al, 2021). Together with our results, this mechanism suggests that the orogenic wedge asymmetry in non-collisional orogens is subject to subduction zone dynamics.…”
Section: Discussionsupporting
confidence: 72%
“…South of our study region, Rodriguez Piceda et al (2020) found that the highest horizontal surface strain rates in the southern Central Andes occur in areas with abrupt variations in crustal density, suggesting an influence of crustal composition and associated rheological properties on short-term deformation. Furthermore, Barrionuevo et al (2021) have shown by means of geodynamic modeling how such variations in crustal composition influence the deformation mode the orogenic wedge.…”
Section: Rheological Model and Active Deformationmentioning
confidence: 99%